(untitled) (Semiárida, 2020)
The objectives of this study were to estimate the growth rate, seasonal distribution of dry matter production and accumulated yield in five cultivars of Bromus catharticus Vahl. and one cultivar of B. parodii Covas et Itria. A secuential cuts methodology was used in a split plot design arranged in random blocks. At each cutting date dry matter yield was estimated. Growth rates were calculated for each mean date, accumulated seasonal yield was estimated and the seasonal distribution patterns were obtained. Growth rates and accumulated yield were analyzed by ANOVA and FLSD tests. B. parodii had lower initial growth rate and higher spring growth rate than B. catharticus. Differences in install growth rates and at the end of winter and beginning of spring were found among B. catharticus cultivars (p<0.05). Accumulated yield was similar for all cultivars (p>0.05).